Suppressor of Cytokine Signaling 1 (SOCS-1) and SOCS-3 Cause Insulin Resistance through Inhibition of Tyrosine Phosphorylation of Insulin Receptor Substrate Proteins by Discrete Mechanisms - Ueki, Kohjiro (American Society for Microbiology, 2004)
Insulin resistance is a pathophysiological component of type 2 diabetes and obesity and also occurs in states of stress, infection, and inflammation associated with an upregulation of cytokines. Here we show that in both obesity and lipopolysaccharide (LPS)-induced endotoxemia there is an increase in suppressor of cytokine signaling (SOCS) proteins, SOCS-1 and SOCS-3, in liver, muscle, and, to a lesser extent, fat. In concordance with these increases by LPS, tyrosine phosphorylation of the insulin receptor (IR) is partially impaired and phosphorylation of the insulin receptor substrate (IRS) proteins is almost completely suppressed. Direct overexpression of SOCS-3 in liver by adenoviral-mediated gene transfer markedly decreases tyrosine phosphorylation of both IRS-1 and IRS-2, while SOCS-1 overexpression preferentially inhibits IRS-2 phosphorylation. Neither affects IR phosphorylation, although both SOCS-1 and SOCS-3 bind to the insulin receptor in vivo in an insulin-dependent fashion. Experiments with cultured cells expressing mutant insulin receptors reveal that SOCS-3 binds to Tyr960 of IR, a key residue for the recognition of IRS-1 and IRS-2, whereas SOCS-1 binds to the domain in the catalytic loop essential for IRS-2 recognition in vitro. Moreover, overexpression of either SOCS-1 or SOCS-3 attenuates insulin-induced glycogen synthesis in L6 myotubes and activation of glucose uptake in 3T3L1 adipocytes. By contrast, a reduction of SOCS-1 or SOCS-3 by antisense treatment partially restores tumor necrosis factor alpha-induced downregulation of tyrosine phosphorylation of IRS proteins in 3T3L1 adipocytes. These data indicate that SOCS-1 and SOCS-3 act as negative regulators in insulin signaling and serve as one of the missing links between insulin resistance and cytokine signaling.